IMPLEMENTATION OF SUPPLY CHAIN MANAGEMENT STRATEGIES IN THE COAL MAZZURY INDUSTRY - Suhendra, Alfan; Yusdartono, Habib Muharry (Bahasa Indonesia, 2024)
Coconut oil processing Virgin Coconut Oil (VCO) is oil that is processed in a simple way without involving synthetic chemicals. Production methods that are commonly carried out on a household scale or micro, small and medium enterprises (MSMEs) include the method of fishing, salting, and fermentation, the Coal Mazzuri industry in Ujung Kubu village produces coconut oil processing Virgin Coconut Oil (VCO). in terms of suppliers to sales so that the raw materials needed do not experience shortages and can facilitate customers in ordering, from the problems faced by researchers implementing Supply Chain Management (SCM) strategies are supply chain management, manufacturing, warehouse/storage, and shops or traders retail, so that the results of this research can help the Coal Mazzuri industry, both in the production and distribution of products that are ready for consumption.